Homogeneous integral controllers for a magnetic suspension system. (April 2020) - Mercado-Uribe, Angel; Moreno, Jaime A.
Abstract: In this work a discontinuous integral controller is applied to a magnetic suspension system to robustly track a time-varying reference, while rejecting non-vanishing time-varying perturbations or uncertainties. Moreover, a family of continuous integral controllers, including a linear one, are derived and its performance is compared with the discontinuous algorithm using both, theoretical arguments, simulations and experiments, performed at a laboratory scale suspension system. The theoretical results are established for the family of controllers using smooth Lyapunov functions. It is shown experimentally that the discontinuous integral controller outperforms the continuous controllers, including the linear one, because it can achieve a high tracking precision for constant and time-varying references in presence of time-varying perturbations and despite of the sensor noise. Moreover, it avoids the limit cycle oscillation caused by the dry friction on the system controlled by the linear algorithm.